Kreativitas Guru PAI Dalam Meningkatkan Keaktifan Siswa Pada Pembelajaran SKI di MTs PP Al-Washliyah Tanjung Haloban Kecamatan Bilah Hilir Kabupaten Labuhanbatu - Priono P; Sokon Saragih; Ahmad Darlis (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to know teachers’ creativity in increasing students’ engagement on Islamic cultural history learning in MTs PP Al-Washliyah Cape Haloban, and the supporting and hindering factors of teachers’ creativity as well as teachers’ learning strategies in increasing students’ engagement. The study used a qualitative method with a descriptive approach. The data collection techniques used were observation, interview, and documentation. The data analysis techniques used in this study were data reduction, data presentation, and inference drawing. The result of this study is to show that teachers’ creativity in increasing students’ activity is classified quite well. Because SKI teachers are able to design and prepare teaching materials, manage classes, peta use creative learning media is possible. The creativity of SKI teachers in enhancing students’ activity was influenced by several Supporting factors namely: (1) means and infrastructure of madrasah, (2) Availability of support from co-teachers and principals, (3) having adequate classrooms or study rooms. So that teachers are able to increase their creativity in improving students. Teachers’ strategies for increasing student activity are in the development of an engaging learning environment that includes creating a creative classroom design, mapping the classroom by changing students’ seating positions into groups, and inviting students to be active. With a good learning environment can affect student activity.